2000
DOI: 10.1034/j.1399-3038.2000.00071.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of IgE‐mediated food allergy among Swiss children with atopic dermatitis

Abstract: Diagnosis of food allergy in children with atopic dermatitis (AD) relies on a good knowledge of the prevalence of the disease and of the foods most frequently involved. Our objective was to define these characteristics in a population-of Swiss children with AD. Patients referred to a pediatric allergist or a dermatologist for AD were routinely tested by skin-prick test (SPT) to seven common food allergens (milk, egg, peanut, wheat, soy, fish, and nuts), and to all other foods suspected by history. Patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
2
14

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(90 citation statements)
references
References 17 publications
4
64
2
14
Order By: Relevance
“…The combination of early, non-eczematous reactions (urticaria, pruritus, and oral allergy syndrome) followed by late-phase flares of eczema is presumably more common; however, the challenge-regimen with massive loading of allergen could prevent this as challenges will be terminated after the initial symptoms. We found that 18 of 122 (14.8%) children with AD had FHS, whereas previous studies have reported more than 30% (4,(8)(9)(10). However, these studies were mainly conducted on selected children recruited from university clinics.…”
Section: Frequency and Relevance Of Sensitizationcontrasting
confidence: 48%
“…The combination of early, non-eczematous reactions (urticaria, pruritus, and oral allergy syndrome) followed by late-phase flares of eczema is presumably more common; however, the challenge-regimen with massive loading of allergen could prevent this as challenges will be terminated after the initial symptoms. We found that 18 of 122 (14.8%) children with AD had FHS, whereas previous studies have reported more than 30% (4,(8)(9)(10). However, these studies were mainly conducted on selected children recruited from university clinics.…”
Section: Frequency and Relevance Of Sensitizationcontrasting
confidence: 48%
“…Deri geçirgenliğinin artması sonucu allerjenlerin daha kolay penetrasyonu ile IgE aracılı sensitizasyon gerçekleşir. Genetik olarak yatkın bireylerde başlayan AD'e infantil çağda %30-60 arasında değişen oranda IgE aracılıklı besin allerjisi eşlik eder (7,8). Bebeklik ve çocukluk yaş grubunda süt, yumurta, buğday, soya, yer fıstığı, fındık gibi besin allerjenleri AD alevlenmelerini tetikleyebilirler (9).…”
Section: Introductionunclassified
“…SPTs usually have sufficient sensitivity and specificity to be the sole method of skin testing necessary for most clinical scenarios. In general, SPTs have a sensitivity of *90 % but a specificity of only about 50 % [22]. An important component of management is the understanding by clinicians of the predictive value of individual FA tests.…”
Section: In Vivo Testsmentioning
confidence: 99%
“…An important component of management is the understanding by clinicians of the predictive value of individual FA tests. The larger the size of the wheal on a skin test, the more likely a patient will react to the food (Table 2) [12,22,23]. The quality and allergen content of the extract employed for the test are pivotal.…”
Section: In Vivo Testsmentioning
confidence: 99%